Acute symptomatic seizures in critically ill children: frequency, etiology and outcomes. - Rajper, Sanam; Moazzam, Mujtaba; Zeeshan, Arsheen; Abbas, Qalab (Journal of Pediatric Neurosciences)
Background: Critically ill individuals have an increased risk of acute symptomatic seizures secondary to systemic illnesses; unrecognized or untreated seizures can quickly convert into status epilepticus, which is associated with high morbidity and mortality. Objective: The aim of this study was to determine frequency, etiology, and outcome of seizures in critical ill children admitted in intensive care unit of a tertiary care hospital. Materials and Methods: Retrospective review of medical records of all children admitted in pediatric intensive care unit (PICU) of the Aga Khan University from January 2016 to December 2018 and who had a new-onset seizure irrespective of underlying diagnosis was carried out after ethical review committee approval. Data were collected on a structured proforma; it included demographic information as well as relevant clinical and outcome information. The data were analyzed on Statistical Package for the Social Sciences (SPSS) software program, version 19.0. The descriptive statistics frequency and percentage was computed for qualitative variable. Mean and standard deviation were computed for quantitative variable, and univariate analysis was performed. Results: During the study period, a total 2053 patients were admitted in the PICU. One hundred six (5%) had seizure. Sixty-three (59.5%) were males. Meningitis 21 (20%), sepsis 21 (20%), complicated pneumonia 18 (17%) were the major primary diagnosis in these children. Mean age of the study population was 75 months (standard deviation [SD] ± 54.4) and 72 (68%) were <5 years of age, whereas 63 (59.5%) were males. The seizures lasted >10min in 10 (10%) and were associated with high had neurological deficit (P = 0.001). We did not observe any correlation with electrolyte imbalance, renal failure, need of ventilator support with duration of seizure, and type of seizure (P > 0.005). Conclusion: Infection was the most common etiology associated with a new-onset seizure in children admitted in our PICU. Seizures lasting for >10min were observed with high neurological deficit. We did not find any association of mortality with seizure duration.